PART IV: Verification of Synchronous Programs - R K Shyamasundar; S Ramesh (Real Time Programming: Languages, Specification And Verification, 2009)
In this part, we will describe important approaches that are used for the verification of programs in synchronous languages like ESTEREL, and Lustre. First we will discuss in detail the verification approaches used for verification of ESTEREL programs. This will be followed by an illustration of verification techniques for LUSTRE programs.